PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE EXAMPLES NON EXAMPLES UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS III SDN 002 BAGAN BATU KEC. BAGAN SINEMBAH - Dedi Afrizal; Damanhuri Daud; Munjiatun Munjiatun (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : Learning outcomes IPS SDN 002 Bagan Batu bagan Sinembah district low, there are still many students who have not reached KKM of 25 students only 10 people who completed (40.00%), while 15 people are not completed (60.00%) is due to students are less involved in the process of learning social studies, students are less motivated to learn IPS, students can not work together with a friend one group, so the learning outcomes to be low. This research aims to improve learning outcomes IPS Grade III SDN 002 bagan Batu bagan Sinembah district 2014/2015 academic year through